2022
DOI: 10.1038/s41420-022-01112-3
|View full text |Cite
|
Sign up to set email alerts
|

RBM47 inhibits hepatocellular carcinoma progression by targeting UPF1 as a DNA/RNA regulator

Abstract: The mechanisms by which the tumor behaviors of hepatocellular carcinoma (HCC) support growth and metastasis remain largely unknown, and it has become increasingly apparent that molecular dysregulation is of considerable importance for cellular signaling pathways. Recently, RNA-binding motif protein 47 (RBM47) has been suggested to function as a tumor regulator by acting as an RNA binding protein (RBP), but its role in HCC remains ambiguous. Here, in HCC, we identified that RBM47 had an inhibitory influence on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 43 publications
(59 reference statements)
0
6
0
1
Order By: Relevance
“…Sakurai T et al [ 32 ] demonstrated that RBM47 suppressed tumor growth of lung adenocarcinoma by inhibiting Nrf2 function. Guo et al [ 33 ] reported that RBM47 acted as a DNA/RNA modulator to inhibit the progression of hepatocellular carcinoma. Qin et al [ 34 ] found that RBM47 suppressed cell proliferation and activated autophagy in papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Sakurai T et al [ 32 ] demonstrated that RBM47 suppressed tumor growth of lung adenocarcinoma by inhibiting Nrf2 function. Guo et al [ 33 ] reported that RBM47 acted as a DNA/RNA modulator to inhibit the progression of hepatocellular carcinoma. Qin et al [ 34 ] found that RBM47 suppressed cell proliferation and activated autophagy in papillary thyroid carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most mRNAs encoding NMD factors themselves have long 3’-UTRs and are targets of NMD, which indicates that their expression is autoregulated [ 35 , 36 ]. Splicing activity in 3’-UTRs significantly increases in tumors, correlates with poor prognosis, and affects many oncogenes [ 37 , 38 ]. Therefore, unproductive splicing is not limited to premature translation termination within the coding frame and has a remarkable regulatory role in the 3’-UTR.…”
Section: Types Of Unproductive Splicingmentioning
confidence: 99%
“…При этом большинство мРНК, кодирующих факторы NMD, сами имеют длинные 3'-НТО и служат мишенями NMD, что указывает на то, что их экспрессия является саморегулируемой [35,36]. Активность сплайсинга в 3'-НТО широко распространена в онкогенах, значительно повышена в опухолях и коррелирует с плохим прогнозом [37,38]. Таким образом, непродуктивный сплайсинг не ограничивается преждевременной терминацией трансляции внутри кодирующей области и обладает значительным регуляторным потенциалом в 3'-НТО.…”
Section: виды непродуктивного сплайсингаunclassified
“…The remaining RBPs identified in this study have no known role in adipose tissue metabolism. Rbm47 has been found to be dysregulated in several types of cancer, including breast, lung, and colorectal cancer [61][62][63][64] . Its aberrant expression has been associated with tumor growth, metastasis, and resistance to therapy.…”
Section: Rbps Of Interestmentioning
confidence: 99%